Cabaran Reformasi Alaf Baru (The Challenge of Reformation in the New Millennium) - Safei, Su'aidi (Terengganu State Foundation Printing, 1998)
Life itself is defined as the reform by getting rid of what is no longer fit for life and replaced it with what is compatible and contemporary. The absence of reform efforts in tandem with the current challenges will lead to the decline and fall behind.